NOVEL APPROACHES FOR DEVELOPMENT OF ORAL CONTROLLED RELEASE COMPOSITIONS OF GALANTAMINE HYDROBROMIDE AND PAROXETINE HYDROCHLORIDE HEMIHYDRATE: A REVIEW - Khatavkar, Umesh Nandkumar; Kumar, K. Jayaram; Shimpi, Shamkant Laxman (International Journal of Applied Pharmaceutics, 2016)
The objective of this review is to study different novel approaches for achieving controlled release for oral administration. There is need of developing cost-effective generic products which will be comparable to the established innovator products with respect to in vivo performance. The innovator products being developed based on exhaustive research are developed utilizing novel platform technologies, have been protected with patents. These platform technologies require specialized manufacturing equipment's and that additionally imparts overall cost to the drug product. This review also contains review on existing technologies utilized for controlling the drug release of actives and also focuses on authors work on the development of cost-effective novel approaches for developing controlled release of some selected central nervous system acting drugs viz galantamine hydrobromide (GAH) and paroxetine hydrochloride hemihydrate (PHH). The existing approved reference products of selected molecules are available based on extended release multi-particulate delivery system and Geomatrix based platform technology for GAH and PHH respectively. This review also explains authors work in developing different controlled release approaches for achieving similar in vivo performance comparable to the reference product. The use of high viscosity grade of hydroxypropyl cellulose (HPC) as a release controlling matrix former in order to control the release of GAH by direct compression into mini tablets offers a feasible dosage form which further can be filled into capsules. Hydroxypropylmethylcellulose (HPMC) based matrix tablets which were further coated using methacrylic acid copolymer were found to be a suitable method to formulate single layer controlled release PHH. Keywords: Paroxetine hydrochloride hemihydrates, Galantamine hydrobromide, Aquacoat, Hydroxypropyl methylcellulose, Geomatrix technology, In vivo